Interpretasi QS. Al-Nisā’ [4]: 34 dalam Wacana Tafsir Feminis: Analisis Pemikiran Husein Muhammad - Malia Hayati, Safira (Nun: Jurnal Studi Alquran dan Tafsir di Nusantara, 2024)
This study examines the reinterpretation of QS. An-Nisā’ [4]: 34 through the lens of Husein Muhammad’s feminist exegesis, combined with Paul Ricoeur’s hermeneutic approach. Traditionally, this verse has often been understood as legitimizing male superiority over women and thus serving as a basis for patriarchy in various spheres of life. Husein offers an interpretation emphasizing sociological-contextual dimensions, suggesting that the verse should be viewed not as a command (‘amr) but rather as a statement (ikhbar) reflecting the patriarchal socio-historical conditions of the sixth century CE. Accordingly, the claim that leadership is exclusively a male prerogative needs to be revisited, given the substantial social transformations that have occurred over time. Ricoeur’s hermeneutics is employed to analyze the symbols and narratives of “leadership” and “women,” which are often confined within patriarchal meaning constructs. Through the stages of distanciation and appropriation, the symbol of leadership can be reinterpreted more inclusively, allowing women to lead without conforming to masculine-biased leadership standards. Likewise, narrative identity invites readers to reconsider the historical accounts of women during the Prophet’s era, who actively engaged in public and political spheres. Findings highlight that Buya Husein’s feminist exegesis enriches interpretations of QS. An-Nisā’ [4]: 34 by integrating text, context, and critical awareness of gender injustice. Viewed through Ricoeur’s hermeneutic framework, this reinterpretation opens broader and more humanistic spaces, enabling the concept of leadership to be realized equally by both men and women. Such equality is not only consistent with religious principles but also aligns with social justice and maqāṣid sharī’ah.